2016
DOI: 10.1002/marc.201600115
|View full text |Cite
|
Sign up to set email alerts
|

Broad Bandgap D–A Copolymer Based on Bithiazole Acceptor Unit for Application in High‐Performance Polymer Solar Cells with Lower Fullerene Content

Abstract: A new broad bandgap and 2D-conjugated D-A copolymer, PBDTBTz-T, based on bithienyl-benzodithiophene donor unit and bithiazole (BTz) acceptor unit, is designed and synthesized for the application as donor material in polymer solar cells (PSCs). The polymer possesses highly coplanar and crystalline structure with a higher hole mobility and lower HOMO energy level which is beneficial to achieve higher open circuit voltage (Voc ) of the PSCs with the polymer as donor. The PSCs based on PBDTBTz-T:PC71 BM blend film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The same group recently designed a 2D‐conjugated D–A copolymer, P69 , by a Stille coupling reaction based on a bithienyl‐benzodithiophene donor and a bithiazole acceptor unit . The P69 copolymer was found to be highly coplanar, with a crystalline structure and low HOMO energy level (−5.21 eV), and a bandgap of 1.96 eV.…”
Section: Bithiazole‐based Polymersmentioning
confidence: 99%
“…The same group recently designed a 2D‐conjugated D–A copolymer, P69 , by a Stille coupling reaction based on a bithienyl‐benzodithiophene donor and a bithiazole acceptor unit . The P69 copolymer was found to be highly coplanar, with a crystalline structure and low HOMO energy level (−5.21 eV), and a bandgap of 1.96 eV.…”
Section: Bithiazole‐based Polymersmentioning
confidence: 99%
“…[52] Due to the electron-withdrawing effect and double non-covalent conformational locks effectively reducing the dihedral angle as compared to Tz-T and T-T of the (BiT) unit, PBDTBTz possessed a lower HOMO level and a highly planar geometry. Therefore, the PBDTBTz:IT-4F-based device obtained a PCE of 7.73% with a V OC of 0.89 V. In 2016, Zhang et al designed and synthesized a new WBG and 2D-conjugated copolymer, PBDTBTz-T. [53] The polymer exhibited a highly coplanar structure and a lower HOMO energy level. The device based on PBDTBTz-T:PC 71 BM blend film achieved a PCE of 6.09% with a relatively higher V OC of 0.92 V. On this basis, in 2017, Zhang et al combining an alkoxylphenyl substituted BDT unit with a bithiazole (BiTunit, synthesized an efficient WBG conjugated polymer (2 eV) PTZ6 with a deep HOMO energy level of 5.36 eV.…”
Section: Tz-based Polymer Donorsmentioning
confidence: 99%
“…[38][39][40] Plenty of D-A copolymers based on BTz as acceptor unit have been reported, showing broad bandgap of ~1.9 eV [41][42][43][44][45][46] and PCEs over 6%. [47] For example, the polymer PBDTBTz-T based on bithiazole and benzodithiphene (BDT) with thiophene conjugated side chins (BDT-T) reported by our group, exhibited a bandgap of 1.89 eV and PCE of 6.09%. [47] Moreover, for the two-dimension (2D)-polymer donor materials based on BDT with conjugated side chains, the absorption spectra and molecular energy levels can be finely modulated by choosing suitable conjugated side chains.…”
Section: Introductionmentioning
confidence: 99%
“…[47] For example, the polymer PBDTBTz-T based on bithiazole and benzodithiphene (BDT) with thiophene conjugated side chins (BDT-T) reported by our group, exhibited a bandgap of 1.89 eV and PCE of 6.09%. [47] Moreover, for the two-dimension (2D)-polymer donor materials based on BDT with conjugated side chains, the absorption spectra and molecular energy levels can be finely modulated by choosing suitable conjugated side chains. [48,49] For example, in previous work, we have shown that attaching meta-alkoxy-phenyl side chains to the BDT unit can make the absorption spectra blue-shifted to some extent and the highest occupied molecular orbital (HOMO) energy level effectively down-shifted in comparison with its counterparts with thiophene side chains.…”
Section: Introductionmentioning
confidence: 99%